A recente interiorização das universidades federais e a questão da democratização do acesso: uma análise das experiências formativas de jovens do semiárido paraibano no Campus de Cuité/UFCG - Silva, Luca Pereira da (2018)
The study presented here turns to the university life in its current profile, in dialogue with the implementation of the public policies of democratization / internalization of the educational spaces in the federal universities. The main objective of the current research is to analyze the formative experiences of university students of the popular stratum, especially those coming from public schools in the semi-arid region of Paraíba, that between 2006 and 2015, they entered, stayed in the campus of Cuité / UFCG and obtained success or outcome in the formation, giving continuity to the studies in a stricto sensu postgraduate (masters and doctorate), thus constructing, a “longstading university trajectory”. The contextual and constitutive specificities of this ongoing process require studies that may support other comparative investigations. For this purpose, assuming the assumptions of a qualitative research, which does not disregard the importance of quantitative elements, we seek to develop a Case Study. The corpus used to analyze the formative experiences are the autobiographical reports sent by 20 former students of the Cuité campus (subjects of the research), identified through a Base Questionnaire, applied through an online platform. The autobiographical report, beyond the traditional autobiographies, are instruments that inform the context of the university practices, observing the construction of a new profile of the Brazilian campus and of a new habitus in the current scenery of the federal universities. The theoretical basis adopted in the study proposes an interface between Social Sciences and Education. In this dialogue, the Sociology of Education is used, starting from Bourdieu and Lahire, referring to the university field, cultural capital, the social origins of the students and the construction of a new habitus in university practices and Sociohistorical Theory, Vygotsky and Leontiev, with the notions of mediation and mediating activities, seeking to understand the construction of the trajectories of formation of students from the relational point of view. Thus, the recent initiatives for the democratization of the access to public higher education are problematized, considering three dimensions: a) democratization of the admission; b) democratization of the permanence conditions and c) academic success or outcome (initial formation and continuity of studies). The analysis points the initiatives and indicators of the ongoing democratization process, showing the State of Paraíba at the forefront of this process in relation to: 1) the gross and net enrollment rates in the population aged 18-24 years; 2) the growth in the number of students enrolled in public institutions from the public school; 3) an increase in number of students who declare themselves as mixed race or black in the federal network 4) to the entrance in the public university by students coming from families of the popular layers; 5) the importance of teacher training and the students' experience in initiation, research, extension, teaching, monitoring, among others, resulting in the construction of their trajectories. It is a delimitation little explored in the study of the contemporary sociabilities with focus in the university formation in its current configuration. The study also questions the meaning of practices in the university and seeks to contribute to the evaluation of Higher Education policies and to the growth of Social Sciences on the approach of the theme.